Exploring cysteine regulation in cancer cell survival with a highly specific "Lock and Key" fluorescent probe for cysteine. Issue 43 (17th September 2019) - Liu, Jing; Liu, Mengxing; Zhang, Hongxing; Wei, Xuehong; Wang, Juanjuan; Xian, Ming; Guo, Wei
Abstract : Using a highly specific "lock and key" fluorescent Cys probe, we confirmed that targeting Cys metabolism to deplete intracellular Cys is a more potent strategy to sensitize cancer cells to chemotherapies. Abstract : To probe the regulatory roles of cysteine (Cys) in cancer cell survival, a highly selective and sensitive fluorescent Cys probe SiR was developed by employing a novel "lock and key" strategy, which allows Cys to be detected without any interference or probe consumption caused by the intracellular high concentration of glutathione (GSH). Using SiR, we confirmed that inhibiting cystine (Cys2 ) transporter system xc − to deplete intracellular Cys is more efficient than inhibiting glutamate–cysteine ligase GCL to deplete intracellular GSH for sensitizing cancer cells to chemotherapy. Moreover, with the probe, a possible self-protection mechanism of cancer cells was indicated: when extracellular Cys sources are blocked, cancer cells could still survive by multidrug resistance protein transporter (Mrp1)-mediated export of intracellular GSH/GSSG as sources to supply intracellular Cys for resisting detrimental oxidative stress. Based on this finding, we further confirmed that abrogating the self-protection mechanism is an even more efficient strategy for sensitizing cancer cells to chemotherapy.